Production, growth, and the environment : an economic approach - Weber, William L. (CRC Press/Taylor and Francis Group, 2014)
Written in a way that facilitates understanding of sometimes difficult concepts and laws, this book discusses the demographic transition and the escape from the Malthusian trap. It also covers the environmental Kuznets curve hypothesis that examines the relation between polluting outputs and economic welfare. The author integrates environmental valuation methods with the production possibility frontier approach. He examines natural resource questions regarding the optimal time to extract non-renewable resources and also examines the optimal harvest rule for renewable resources such as timber and fisheries.